Significant learning assessment model using digital badges: A case study in the systems engineering program of El Bosque University (2021)
In the Colombian university context engineering curricula are designed aimed to develop competencies, obeying national and international standards. In the context of the El Bosque University Systems Engineering program, in addition to these competencies, students are expected to develop six kinds of learning, according to the Significant Learning taxonomy. Nonetheless, the majority Faculties assessment systems are numeric-grades based and do not retrieve information about the achievement level of such competencies or kinds of learning. Based on the background review and interviewing curriculum designers, this work presents the process for constructing a continuous assessment model responding to this need, using Digital Badges. The model is presented through two main results: A conceptual network of relations between each problematic nucleus competencies that are expected to achieve, and the six dimensions of significant learning. The second result is a two-dimensional digital badges network which determines what badges should be awarded and when to award them.